Development of a new multiplex quantitative real‐time PCR assay for the detection of the mtDNA4977 deletion in coronary artery disease patients: A link with telomere shortening. (24th May 2013) - Sabatino, Laura; Botto, Nicoletta; Borghini, Andrea; Turchi, Stefano; Andreassi, Maria Grazia
<x xml:space="preserve">Abstract</x> Mitochondrial DNA (mtDNA) and telomere shortening have been proposed as important contributors to vascular disease and atherogenesis. The role of mitochondrial and telomere alterations has been examined frequently, but usually separately. Recently, an integrated model in which DNA damage and metabolic pathways intersect in age‐associated cardiovascular disease has been proposed. In this study we developed a fast and reliable real‐time PCR‐based procedure to investigate relative quantification of the 4, 977 bp mitochondrial DNA deletion (also indicated as "mtDNA4977 deletion"), employing TaqMan probes with a multiplex approach. As a validation of the assay, a nested PCR coamplification was performed. Telomere shortening was evaluated by a real‐time monochrome multiplex PCR technique employing a SybrGreen‐based analysis. The study of mtDNA4977 deletion and telomere shortening was carried out in atrial biopsies from 11 patients undergoing coronary artery (n = 5) and valve surgery (n = 6). The relative quantifications showed that the amount of mtDNA4977 deletion was greater in tissue of patients with coronary artery disease (CAD) (P = 0.01) and that telomere length (expressed as telomere length relative to a single copy reference gene) was significantly shorter in tissue of CAD patients, compared to patients without CAD (P = 0.03). Moreover, most conventional risk factors were significantly more frequent in CAD patients, smoking and dyslipidemia having the strongest association with the degree of mtDNA4977deletion and a significant correlation with telomere attrition (P = 0.02 and P = 0.006, respectively). In conclusion, the present study suggests that mtDNA4977 deletion and telomere shortening may represent additional and synergic major risk factors for the pathogenesis of CAD and its complications. Environ. Mol. Mutagen. 54:299–307, 2013. © 2013 Wiley Periodicals, Inc.